2018
DOI: 10.1245/s10434-018-6501-y
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Incidentalomas During Diagnostic Work-up of Colorectal Cancer Patients: What is the Risk of Metastases?

Abstract: This is the first study to report on adrenal incidentalomas in CRC patients. In newly diagnosed CRC patients without disseminated disease, AIs can be considered benign, and no additional imaging is indicated to rule out adrenal metastases in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
5
7
0
Order By: Relevance
“…These results support the previously reported prevalence of adrenal incidentalomas discovered during follow-up of patients with colorectal carcinoma (6.8%-10.5%) ( 14 , 15 ). Similarly, most of those reported lesions were non-metastatic.…”
Section: Discussionsupporting
confidence: 92%
“…These results support the previously reported prevalence of adrenal incidentalomas discovered during follow-up of patients with colorectal carcinoma (6.8%-10.5%) ( 14 , 15 ). Similarly, most of those reported lesions were non-metastatic.…”
Section: Discussionsupporting
confidence: 92%
“…Thyroid carcinoma accounted for only 0.8% of the primary lesions in patients with AM in this study. In terms of the staging of extra-adrenal malignancies, patients with AM were more likely to be in the late stage, while those with ABM were more likely to be in the early stage, which is consistent with the findings of previous studies ( 8 , 15 , 16 ).…”
Section: Discussionsupporting
confidence: 91%
“…A recent population-based cohort study reported a 7.5% prevalence of metastasis in AIs, and that malignancy was 22 times more likely when the AI was discovered during cancer staging [ 8 ]. In patients with Colo-Rectal Cancer, the incidence of AIs was 10.5% (in 475 subjects); however, adrenal metastases could be ruled out in most cases (96%) with CT re-evaluation, follow-up imaging and multidisciplinary evaluation [ 9 ]. However, it is personal opinion of the authors that if an imaging study was performed during the evaluation of known extra-adrenal cancer, the AI does not fall into the definition of “incidentaloma”, because the imaging itself has been performed in a patient with an active malignancy, therefore the pre-test probability that the adrenal lesion represents a metastasis is high.…”
Section: Question 1: Is It Malignant?mentioning
confidence: 99%